Long-range transport of airborne microbes over the global tropical and subtropical ocean - Eva Mayol; Jesús M. Arrieta; Maria A. Jiménez; Adrián Martínez-Asensio; Neus Garcias-Bonet; Jordi Dachs; Belén González-Gaya; Sarah-J. Royer; Verónica M. Benítez-Barrios; Eugenio Fraile-Nuez; Carlos M. Duarte (Nature Communications, 2017)
The extent to which the ocean acts as a sink and source of airborne particles to the atmosphere is unresolved. Here, the authors report high microbial loads over the tropical Atlantic, Pacific and Indian oceans and propose islands as stepping stones for the transoceanic transport of terrestrial microbes..